PEMBUATAN ALAT PERAGA ELEKTRO PNEUMATIK SEBAGAI MEDIA PEMBELAJARAN - Nurudin, Muchamad (Politeknik Harapan Bersama Tegal, 2024)
The very rapid technological developments in the industrial world must also be accompanied by the development of world education, therefore the Mechanical Engineering Study Program of the Joint Hope Polytechnic of Tegal City provides courses on Pneumatic and Hydraulic Systems to bridge automation system students, but in the implementation of the teaching and learning process based on the results of understanding Researchers openly to students, can deny that the teaching and learning process lacks visualization tools. Seeing this condition, the researcher aims to build an automation system tool that combines a full pneumatic trainer control system and an electro-pneumatic trainer system using the analytical method. these components consist of 1). Double acting cylinder, 2). Single acting cylinder, 3). Air regulator with flow meter, 4). 5/2 Selenoid valve 220 VAC and 3/2 selenoid valve 220 VAC, 5). Limit switch, 6). Proximity sensor, 7). Push-button switch, 8). 24 VDC DC relay, 9). Pilot lamp, 10). Power supply unit 220 VAC, VDC, 11). Air filter regulator, the material for the electro-pneumatic trainer frame uses 4x4 mm hollow iron and aluminum profiles, 1100mm high, 1000mm long, A4 size 5mm acrylic material. The results of the design and development using the analytical method obtained an electro-pneumatic electro-pneumatic trainer system which visualizes the teaching and learning process of mutual hope polytechnic students.